دور التمكين الموارد البشرية في تحقيق األداء المتميز –دراسة حالة مؤسسة النقل الحضري وشبه الحضري سوق اهراس- - نجم الدين خوايجية (My University, 2024)
The topic of human resources empowerment is considered one of the modern administrative topics that has gained the attention of researchers.This study aimed to shed light on the role of empowering human resources in achieving outstanding performance,as a new culture that institutions seek to adopt in order to raise the level of employees by involving them in formulating the organization’s goals through a set of dimensions. It was represented by sharing information and providing communication channels, freedom and independence in making decisions, forming self-work teams to facilitate the exchange of experiences between employees, and finally delegating authority from senior management, and on the other hand, bringing the employees’ performance to outstanding performance in order to achieve a lasting competitive advantage and become more flexible and responsive. To changes in the external environment. يعتبر موضوع تمكين الموارد البشرية من المواضيع الإدارية الحديثة والتي أصبحت تحظى باهتمام الباحثين. حيث هدفت هذه الدراسة الى تسليط الضوء على دور تمكين الموارد البشرية في تحقيق الأداء المتميز. باعتباره ثقافة جديدة تسعى المؤسسات الى تبنيها بغية الرفع من مستوى العاملين من خلال اشراكهم في صياغة اهداف المؤسسة عن طريق مجموعة من الابعاد تمثلت في المشاركة في المعلومات وتوفير قنوات اتصال، الحرية والاستقلالية في اتخاذ القرارات، تكوين فرق العمل الذاتية لتسهيل تبادل الخبرات بين العاملين وأخيرا تفويض السلطة من طرف الإدارة العليا ومن جهة أخرى الوصول بأداء العاملين الى أداء متميز من اجل تحقيق ميزة تنافسية دائمة وتصبحأكثرمرونةواستجابةلتغيراتالبيئةالخارجية. Le thème de l’autonomisation des ressourceshumainesestconsidérécommel’un des sujetsadministratifsmodernes qui a retenul’attention des chercheurs. Cetteétudevisait à mettre en lumière le rôle de l’autonomisation des ressourceshumainesdansl’obtention de performances exceptionnelles, en tantque nouvelle culture que les institutions cherchent à adopter afind’élever le niveau des employés en les impliquantdans la formulation des objectifs de l’organisation à travers un ensemble de dimensions. Cela a étéreprésenté par le partaged'informations et la fourniture de canaux de communication, la liberté et l'indépendancedans la prise de décision, la formation d'équipes de travail autonome pour faciliterl'échanged'expériences entre les employés, et enfin la délégation de l'autorité de la haute direction, et d'autre part, la mise en relation des employés. performance à des performances exceptionnellesafind'obtenir un avantageconcurrentiel durable et de devenir plus flexible et réactif. Aux changementsdansl'environnementextérieur.
Keywords: Keywords: empowerment; human resources; outstanding performance; empowering human resources.; كلمات مفتاحية:التمكين،الموارد البشرية،الأداء المتميز،تمكين العاملين.; Mots-clés:responsabilisation; ressourceshumaines; performance exceptionnelle; responsabilisation des ressourceshumaines.